Developing an understanding and improved sensory quality of low alcohol beer - Ramsey, Imogen (2021)
The international non-alcoholic beer (NAB) market is predicted to be worth over $25bil by 2024. Consumers across the globe are limiting their alcohol consumption due to changes to healthier lifestyles and increased knowledge of long-term effects of alcohol. Research has shown however, that consumers find NABs ‘bland’, ‘disappointing’ and ‘less tasty’ than their higher alcohol counterparts. Consequently, the development of a NAB that displays similar sensory pleasure to its higher alcohol counterpart is an attractive proposition to manufacturers and consumers alike. This research therefore aimed to understand both the sensory and physicochemical role of ethanol in beers with different ethanol concentrations and within a range of commercially produced NABs, whilst also identifying the overall effect on consumer liking. Furthermore, investigations into the effect of physical dealcoholisation techniques (namely reverse osmosis) on the sensory and physicochemical properties of two different beer styles were assessed. To achieve these aims, four studies were employed.